The Influence of Cartoon Film Media on Story Listening Skills and Cognitive Learning Outcomes - Hilda Putri Anggraini; Muhammad Abduh (STAI Hubbulwathan Duri, 2023)
The objective of this study is to ascertain the impact of utilising cartoon film media on the development of listening skills and cognitive learning outcomes in the context of Indonesian language content. The research methodology employed is quantitative research utilising a quasi-experimental research model, specifically employing a pretest-posttest control group design. The population under investigation comprised 60 pupils who were all in class III at a public elementary school located in Karanganom, Klaten. Sampling in this study was purposive sampling, meaning that it is based on certain characteristics which are seen as having a close relationship with the characteristics of the population. The sample was chosen because it has the ability to homogeneous student criteria. Instrument tests carried out research analysis in the form of validity and reliability tests, prerequisite tests consisting of normality tests and homogeneity tests, and hypothesis testing in the form of paired sample t-tests. The findings of this study suggest that the utilisation of cartoon film media has a significant impact on the enhancement of listening skills and cognitive learning outcomes among individuals from Indonesia. The data presented is derived from the learning outcomes of the experimental group, which had a pretest mean score of 73.83 and a posttest mean score of 82.66. Similarly, the control group had a pretest mean score of 73.00 and a posttest mean score of 81.50. The evaluated numerical data reveals that there are three students who have achieved exceptional performance, with scores over 80%. Additionally, 18 students have obtained high scores ranging from 60% to 80%, while nine students have achieved scores in the lower range of 40% to 60%.